Analysis of Access to Formal Credit Financial Technology for Chili Farmers in Sukabumi District - Hasvi, Ismail; Sarah anistia (JURNAL AGRICA, 2025)
Banking is a financial institution that drives the economy of society, including agricultural producers. The financial literacy index in 2014 showed a very low value of 65.43%. Limited financial literacy hinders farmers' ability to access formal credit institutions such as banks. Financial technology has emerged as an alternative to make it easier for farmers to access sources of financial financing. This study aims to examine the impact of farmer characteristics, financial literacy, and financing service quality on access to formal credit, along with the determinants that influence access to formal credit in financial technology. This study was conducted in Kabandungan District, Sukabumi Regency. The research methodology used was a mixed method, with a total of 100 farmer participants from Kabandungan District. The analysis methods used are descriptive and qualitative analysis, utilizing Microsoft Excel, SPSS, and Smart PLS software. The t-statistic value shows that farmer characteristics with a t-statistic value of 4.48 and financial literacy with a t-statistic value of 11.25 have a significant effect on access to formal credit and financing quality in Financial Technology financing.